FRET-based carbazole-fluorescein ionic nanoparticle for use as an effective bioimaging agent - Amanda Jalihal; Hannah Krehbiel; Samantha Macchi; Mavis Forson; Mujeebat Bashiru; Thuy Le; Caroline Kornelsen; Noureen Siraj (Biofunctional Materials)
Fӧrster resonance energy transfer (FRET)-based systems are widely applicable in many areas of interest. In this study, a novel FRET-based ionic material (IM) was synthesized by pairing carbazole imidazolium cation (CI+) with fluorescein anion (Fl2-) through a simple ion-exchange method. The resulting IM ([CI]2[Fl]) was converted into an ionic nanoparticle (INP) in aqueous media for practical use for bioimaging application. The photophysical properties of the parent dyes, [CI]2[Fl], and INP were studied in detail. All FRET parameters were calculated in the synthesized material. [CI]2[Fl] exhibited a significant spectral overlap integral and an ideal theoretical FRET distance. The presence of the FRET mechanism was verified by the observed decrease in donor fluorescence lifetime and a moderate FRET efficiency in [CI]2[Fl]. The INP formed from [CI]2[Fl] was evaluated for use as a fluorescent pH probe and bioimaging agent. FRET efficiency of INP is calculated in a series of pH studies which indicates the highest efficiency at physiological pH. Whereas no FRET phenomenon is observed in highly acidic and basic conditions. The pH-dependent photophysical properties of [CI]2[Fl] are monitored and allow for the potential application as a fluorescent probe for the detection of acidic tissues in biological systems. The FRET-capable INP showed superior bioimaging capability in vitro as compared to the parent dye.